2015
DOI: 10.1016/j.ijid.2015.07.022
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of syphilis, human immunodeficiency virus, hepatitis B virus, and human T-lymphotropic virus infections and coinfections during prenatal screening in an urban Northeastern Brazilian population

Abstract: Syphilis was twice as prevalent among pregnant women in Maceió, compared to the national average, and coinfections with syphilis/HIV and HTLV/HBV were significantly associated among these pregnant women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
14
0
7

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 17 publications
(22 reference statements)
5
14
0
7
Order By: Relevance
“…The present study reported for the first time the serological profiles for HTLV, HIV, HBV, CMV and rubella in pregnant adolescents who received care in the city of Belém, Pará, northern region of Brazil. Although the prevalence of HTLV in the study population (0.6%) was within the range previously observed in other populations in the state of Pará [ 24 , 25 ], we considered the prevalence high compared to other studies performed in pregnant women in the state of Pará [ 13 ] and other locations in Brazil, including Manaus [ 12 ], Maranhão [ 26 ], Paraná [ 18 ] and Maceió [ 23 ]. This finding is worrying because it indicates early contact of young women with an agent whose screening is not included in the prenatal tests and whose main forms of transmission include breastfeeding.…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…The present study reported for the first time the serological profiles for HTLV, HIV, HBV, CMV and rubella in pregnant adolescents who received care in the city of Belém, Pará, northern region of Brazil. Although the prevalence of HTLV in the study population (0.6%) was within the range previously observed in other populations in the state of Pará [ 24 , 25 ], we considered the prevalence high compared to other studies performed in pregnant women in the state of Pará [ 13 ] and other locations in Brazil, including Manaus [ 12 ], Maranhão [ 26 ], Paraná [ 18 ] and Maceió [ 23 ]. This finding is worrying because it indicates early contact of young women with an agent whose screening is not included in the prenatal tests and whose main forms of transmission include breastfeeding.…”
Section: Discussionmentioning
confidence: 61%
“…Our results are in agreement with data from the Ministry of Health that note a higher number of cases of HIV-1 infection in women between the ages of 20 and 24 years [ 5 ]. In Brazil, other studies in non-adolescent pregnant women demonstrated a low seroprevalence of HIV-1 infection [ 7 , 23 , 27 , 28 ], which differed from reports from other developing countries, where the prevalence of infection was greater than 5% [ 29 31 ].…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…Most of these mothers with syphilis in our study were migrants, unemployed or illiterate, which might have increased the risk of infection and the likelihood of missed active interventions. Moreover, syphilis was subjected to HIV/STD coinfection as previously reported 21. Stigma and isolation might pose obstacles to screening and antenatal care.…”
Section: Discussionmentioning
confidence: 88%
“…HIV prevalence in women during antenatal care in 2007 in Sergipe state was found to be 0.09% amongst women aged 10-19 (95%CI: 0.01-0.3) [40]. In Maceio, AL between 2007 and 2012, the HIV prevalence amongst pregnant women aged 15-26 years was 0.3% [41]. A nationwide analysis of 15-24 year-old women in labor in 2009 found a prevalence of 0.7% (95%CI: 0.4–1.1) [42].…”
Section: Resultsmentioning
confidence: 99%